2019
DOI: 10.1007/s42399-019-00181-3
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of the Krio Version of the WHOQOL-BREF for Use in Sierra Leone

Abstract: Formal measures of subjective well-being are needed to assure that health and psychosocial support services in Sierra Leone are objectively evaluated and evidence-based. The purpose of this study was to evaluate a Krio version of the brief form of the World Health Organization's Quality of Life (WHOQOL-BREF) questionnaire. A convenience sample of 425 adult Sierra Leoneans was verbally interviewed in the northern province of Bombali, using a previously piloted version of the scale, as well as a short demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…The EQ-5D-3L Interviewer Administered v2.1 was translated into Krio for Sierra Leone using an expanded methodology based on the EuroQol Foundation guidelines [ 18 ] including focus groups, a process of iterative forward and backward translation, two independent forward translations and two independent back translations, followed by review and reconciliation. EQ-5D-3L was selected instead of the EQ-5D-5L due to difficulties of translating the five levels into Krio and difficulties in discriminating between the five levels with similar issues experienced by other researchers [ 19 ]. The translated tool can be accessed here [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The EQ-5D-3L Interviewer Administered v2.1 was translated into Krio for Sierra Leone using an expanded methodology based on the EuroQol Foundation guidelines [ 18 ] including focus groups, a process of iterative forward and backward translation, two independent forward translations and two independent back translations, followed by review and reconciliation. EQ-5D-3L was selected instead of the EQ-5D-5L due to difficulties of translating the five levels into Krio and difficulties in discriminating between the five levels with similar issues experienced by other researchers [ 19 ]. The translated tool can be accessed here [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…A four-point scale was used in an attempt to balance sensitivity with simplicity. Price, Conteh and Esliker [ 30 ], in their translation of the WHOQOL-BREF into Krio, found that some of the extreme anchor points in a five-point scale required the creation of terms that are not commonly used in Krio, raising questions of whether individuals are able to distinguish between the different options.…”
Section: Methodsmentioning
confidence: 99%
“…It is also in line with Betancourt's [44] observation that more concrete items tend to be more easily understood in a scale. Price, Conteh & Esliker [30] also noted that in Krio, psychological constructs are not easily separated from physical ones. A related challenge (also noted by Kaiser et al [21]) is that, particularly when trying to describe relatively abstract concepts, items sometimes became relatively long and difficult to follow.…”
Section: Understandings Of Distress In Sierra Leonementioning
confidence: 99%